A case report of PGAP2-related hyperphosphatasia with impaired intellectual development syndrome in a Chinese family and literature review - Pan, Yijun; Ren, Bin; Chen, Lijuan; Li, Qiang (Frontiers in Pediatrics, 2024)
Recently, mutations have been identified in six genes (PIGA, PIGY, PIGO, PGAP2, PIGW and PGAP3) encoding proteins in the Glycosyl phosphatidylinositol(GPI)-anchor-synthesis pathway in individuals with hyperphosphatasia with impaired intellectual development syndrome(HPMRS).Reports involving the rare pathogenic gene, post-GPI attachment to proteins 2 (PGAP2) are quite limited. In this study, we reported two patients with PGAP2 variants related neurodevelopmental disorders from Asian population. The proband, onset of epileptic spasms at 5 months, concurrently with global developmental dalay, facial malformation and elevated alkaline phosphatase. His younger sister, onset of epileptic spasms at 2 months, having similar clinical features as the proband.Their phenotypes are consistent with PGAP2 related diseases. The two missense variants (c.686C＞ T (p.Ala229Val) and c.677C＞T (p.Thr226Ile) ) in PGAP2 gene found in this family were segregation with the disease, while c.677C＞T (p.Thr226Ile) was a novel variant. All the two patients showed a positive response to ACTH treatment and high-dose pyridoxine. In summary, this study contributes to expanding the pathogenic variant spectrum of PGAP2 related HPMRS, and provides new insights into the treatment.